THE IMPACT OF PSYCHOLOGICAL CAPITAL ON THE FORMATION OF POSITIVE BEHAVIOR IN THE WORKPLACE - Hovhannisyan , A.A. (Modern Psychology, 2020)
In a rapidly changing world it is crucial to establish and maintain a sustainable relationship between employees and employers. Corporations are looking for employees who will demonstrate positive work behavior at workplace and self- confidence in their careers. An employee who demonstrates self-confidence in career can overcome obstacles, strives for self-education, is self-sufficient in career choices, and is willing to move forward. An employee with a positive work ethic is willing to work beyond their defined roles and creating a strong and positive relationship with the organization and teammates. All of this positively affects both the individual, the organization, and teammates by creating a healthy work environment. In this article, we have discussed the formation, strengthening and development of self-confidence in career shaping. We have also defined what psychological capital is (Psycap) and have determined its relation to the positive work behavior. Psycap which is one of the branches of positivist research. The article also analyzes the role of emotional intelligence and its impact on self-confidence in career and on positive work behavior. Literature analysis has shown that there is a positive correlation between psychological capital, positive work behavior, and self-confidence in careers, and in fact, that emotional intelligence has a significant influence on all of this.
Keywords: positive psychology; psychological capital; organizational positive behaviour; emotional intelligence; career confidence